MRI Otak Demensia: Protokol RSUP Dr. Sardjito Yogyakarta - Dedi Hardianto; Fatimah Fatimah; Marichatul Jannah (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: The procedure for examining brain magnetic resonance imaging (MRI) in clinical dementia at the Radiology Installation of RSUP dr. Sardjito Yogyakarta used T2W, 3D FLAIR, 3D FFE ADNI, diffusion weighted imaging (DWI) and susceptibility weighted imaging (SWI) sequences.  The selection of this sequence was in accordance with the existing references, but was added with the SWI sequence. This study aims to determine the MRI brain examination in clinical dementia and to find out the reason for the addition of the SWI sequence.Methods: This type of research is a qualitative research with a case study approach. Data was collected by observation, in-depth interviews and documentation. Data analysis was carried out with the stages of data transcription, data reduction, data presentation and carried out discussions and drawing conclusions.Results: The results of the study stated that the measurement of brain volume was carried out by entering the raw data of the T1 FFE ADNI sequence image into the freesurfer software which was useful for assessing Alzheimer's dementia.Conclusions: The diagnosis is made by looking for bleeding and microbleeding using the SWI sequence in assessing vascular dementia. SWI sequences are useful in differentiating between calcification and microbleeding causing vascular dementia.